Gilbert & George : The Art of / or an aesthetic of existence - Jahn, Wolf (New York : Thames and Hudson, 1989)
In this, the first full-length illustrated exposition of the art of Gilbert & George, Wolf Jahn traces its development by setting it in the widest possible cultural context. With the help of over 400 reproductions - 291 in superb color - he shows how Gilbert & George first embodied in themselves the plight of their own age - the impasse of modernism, with its crisis of values and its imitations of the lifeless rigility of a dehumanized environment - and then embarked on a symbolic process of decline, plainly documented in their works. They emerged into a new world of their own, based on sexual polarities and blazing with life ang growth.
bibliog. p. 503-516
biog., tent. p. 489-501
Engels
boek
Keywords: Gilbert & George